Feasibility of computed tomography‐guided core needle biopsy in producing state‐of‐the‐art clinical management in Chinese lung cancer. Issue 2 (March 2014) - Chen, Hua‐Jun; Yang, Jin‐Ji; Fang, Liang‐Yi; Huang, Min‐Min; Yan, Hong‐Hong; Zhang, Xu‐Chao; Xu, Chong‐Rui; Wu, Yi‐Long
Abstract Background A satisfactory biopsy determines the state‐of‐the‐art management of lung cancer in this era of personalized medicine. This study aimed to investigate the suitability and efficacy of computed tomography (CT)‐guided core needle biopsy in clinical management. Methods A cohort of 353 patients with clinically suspected lung cancer was enrolled in the study. Patient factors and biopsy variables were recorded. Epidermal growth factor receptor (EGFR) gene mutations and echinoderm microtubule‐associated protein‐like 4 (EML4)‐anaplastic lymphoma kinase (ALK) rearrangement were detected in tumor specimens. Adequacy of biopsic obtainment for clinical trial screening and tissue bank establishment were reviewed. Results Overall diagnostic accuracy of malignancy achieved 98.5%. The median biopsy time of the cohort was 20 minutes. In patients with non‐small cell lung cancer (NSCLC), 99.3% (287/289) were diagnosed as specific histologic subtypes, and two patients (0.7%) were determined as NSCLC not otherwise specified (NOS). EGFR mutations were analyzed in 81.7% (236/289) of patients with NSCLC, and 98.7% (233/236) showed conclusive results. EML4‐ALK gene fusion was tested in 43.9% (127/289) of NSCLC patients, and 98.4% (125/127) showed conclusive results: 6.4% (8/125) of those had gene fusion. Ninety‐six NSCLC patients participated in clinical trial screening and provided mandatory tumor slides for molecular profiling. Pathological evaluation was fulfilled in 90 patients (93.8%); 99.4% (320/322) of patients with malignancy provided extra tissue for the establishment of a tumor bank. Conclusions CT‐guided core needle biopsy provided optimal clinical management in this era of translational medicine. The biopsic modality should be prioritized in selected lung cancer patients.